solve by completion of square method 5x square-6x-2
pls fast
Answers
Answered by
5
Hi ,
It may be like this ,
5x² - 6x - 2 = 0
divide each term with 5, we get
x² - 6x/5 - 2/5 = 0
=> x² - 6x/5 = 2/5
=> x² - 2 × x × ( 3/5 ) = 2/5
=> x² - 2x( 3/5 ) + ( 3/5 )² = 2/5 + ( 3/5 )²
=> ( x - 3/5 )² = 2/5 + 9/25
=> ( x - 3/5 )² = ( 10 + 9 )/25
=> ( x - 3/5 )² = 19/25
=> x - 3/5 = ± ( √19 )/5
x = 3/5 ± ( √19 )/5
x = ( 3 ± √19 )/5
Therefore ,
x = ( 3 + √19 )/5 or x = ( 3 - √19 )
I hope this helps you.
: )
It may be like this ,
5x² - 6x - 2 = 0
divide each term with 5, we get
x² - 6x/5 - 2/5 = 0
=> x² - 6x/5 = 2/5
=> x² - 2 × x × ( 3/5 ) = 2/5
=> x² - 2x( 3/5 ) + ( 3/5 )² = 2/5 + ( 3/5 )²
=> ( x - 3/5 )² = 2/5 + 9/25
=> ( x - 3/5 )² = ( 10 + 9 )/25
=> ( x - 3/5 )² = 19/25
=> x - 3/5 = ± ( √19 )/5
x = 3/5 ± ( √19 )/5
x = ( 3 ± √19 )/5
Therefore ,
x = ( 3 + √19 )/5 or x = ( 3 - √19 )
I hope this helps you.
: )
Answered by
0
(3 - √19)
is the answer
hope this is help you
is the answer
hope this is help you
Similar questions
Social Sciences,
8 months ago
Hindi,
8 months ago
Physics,
8 months ago
Social Sciences,
1 year ago
English,
1 year ago
Math,
1 year ago
Math,
1 year ago